A Contextual Interpretation of the Book of Micah: Social Justice and Marginalized People in Indonesia - Kurniawan, Dodi (Hikmat : Jurnal Agama Kristen, 2025)
This study interprets the Book of Micah contextually to formulate a public ethics relevant to social justice in Indonesia, particularly for marginalized groups such as indigenous communities, urban informal workers, coastal communities, and religious minorities. Using a qualitative design-Using an interpretive approach with an abductive flow, the research combines exegesis (Micah 2:1–5; 3:1–12; 6:6–8; 7:1–7) and socio-policy analysis of Indonesia (2015–2025) through open/thematic/axial coding, source triangulation, and the frameworks of liberation theology, postcolonial hermeneutics, and public theology. The results demonstrate Micah's three ethical axes—doing justice,ḥesed (loyalty/solidarity), and humility before God—resonate with issues of land grabbing, judicial corruption, unequal access to basic services, and the crisis of leadership integrity. The research's main contribution is the development of a Theological-Policy Translation Matrix that links exegetical findings with policy issues, key actors, practical recommendations (e.g., legal aid clinics, customary-based mediation, open budget forums, citizen education), and evaluation indicators (accountability, participation, inclusiveness). The findings confirm thatḥESD does not stop at individual compassion, but rather demands a just and auditable social architecture. Limitations of the study include the illustrative nature of the data and the need for policy updates. Moving forward, the development of Micah's cross-sector justice indicators and longitudinal testing of intervention effectiveness are recommended to strengthen the transformative impact of prophetic interpretation in Indonesian public practice.